Implementasi Metode Manhaji sebagai Inovasi Pembelajaran Nahwu di PPTQ Lentera Qur'ani Mojogedang - Fityatun Naffa; Kafin Jaladri (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2026)
Nahwu learning is often perceived as a difficult and tedious subject for beginner students. This study aims to describe the implementation of the Manhaji method and to examine students’ responses and its impact on nahwu learning at PPTQ Lentera Qur’ani Mojogedang. This research employed a descriptive qualitative approach involving seventh-grade students as the research subjects. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles and Huberman. The findings showed that the Manhaji method was implemented through systematic stages of preparation, implementation, and evaluation. Learning activities were conducted gradually by using contextual examples from Qur’anic verses and reinforcing grammatical rules through Manhaji songs. Students showed positive responses indicated by increased attention, enthusiasm, and participation during the learning process. Cognitively, the method helped students understand basic nahwu concepts, while affectively it increased learning motivation and self-confidence. The findings suggest that the Manhaji method has the potential to serve as an alternative approach for teaching nahwu to beginner learners, particularly in tahfizh-based Islamic boarding school environments with limited learning time and learning resources.